Adrenomedullin receptors: molecular identity and function - Hay, Debbie L; Smith, David M (Peptides (New York, N.Y. : 1980), 2001)
Since its discovery in 1993 adrenomedullin (AM) has been the subject over 600 published articles. This multifunctional peptide has powerful vasodilator actions and recent evidence from AM gene-deleted mice suggest that AM plays an essential role in vascular development. However the lack of valid AM receptor clones and non-peptide receptor ligands has considerably slowed research progress on this important peptide. In this review we have focused on the proposition that the calcitonin receptor-like receptor (CRLR) is a receptor both for AM and the related vasoactive peptide calcitonin gene-related peptide (CGRP). The receptor activity modifying proteins (RAMPs) that are essential for defining CRLR pharmacology will also be discussed. We will describe how AM receptors have been reported to signal and be regulated and to consider whether further receptors for AM beyond CRLR/RAMP combinations might exist.